Goat Pneumonia in the district of Pieria (Greece) - ΣΤΕΦΑΝΟΥ Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A total of 1410 lungs of goats, which were slaughtered in the district of Pieria (Greece), were examined macroscopically. Out of them, 207 were subjected, also, to histologic. 34 to microbiological and 50 to parasitological examinations. Parasitic infections were very commonly accountied on 87 % of the cases. M. capi Maris, P. rufescens and D. filaria were the species isolated. M. capillaris was isolated in the majority of the cases. Macroscopic lesions were primarily represented by various size areas of hepatosis, especially in the diafragmatic lobes. Microscopic changes were those of bronchopneumonia or IobuIar.pneuoionia. In 18 cases enzootic pneumonia due to Pasteurella sp. was observed. Pasteurella haemolitica was isolated in 6 cases and Pasteurella multocida in three cases. In three more cases diagnosis was based on macro-and microscopic changes. Macroscopic lesions, as a severe hepatosis, were concentrated mainly on the right apical lobe. The microscopic picture revealed bronchiolar and alveolar changes characterised by cellular exudate consisting of macrophage cells. Thus, the pneumonia was lobular or fibrinous one. In 40 cases changes of interstitial pnemonia with inclusion bodies resembling those caused by P.L.V. (Chlamydia) were observed. The changes in these cases were lobulary distributed and were located mainly in the right apical lobe. In the microscopic examination, were observed interstitial pneumonia with perivascular and peribronchial changes characterised by infiltration with histiocytes and lymphocytes. In the epithelial bronchi and bronchial glands there were found endoplasmic eosinophilic inclusion bodies. Finally in three cases adenomatosis of the lungs resembling that of the sheep was observed· In these cases the changes were multicentral consisting of multiple white or white-gray nodes, 5-10 mm in diameter and compact in consistancy. Histologically, papillomatous tissue «asobserved, predominantly in the alveolar and bronchial epithelium, and also, vacuole degeneration of the high columnar epithelium.